A linear control approach to design digital speed control system for PMSMs - Yuan, Xin (2022)
In order to pursue the high performance of speed control for permanent magnet synchronous machines (PMSMs), a digital speed control system is proposed. In the proposed structure, two parts, namely speed controller and speed measurement have been designed compared with the conventional speed control scheme. The proposed universal instantaneous speed observer is regarded as the speed measurement, where it can unify other types of speed observers, eliminate delay issue and reduce measurement noises by utilizing the merit of high order system characteristic. The proposed speed controller with active damping structure is able to decouple the current loop bandwidth effect on speed system, meanwhile possesses better dynamic response, disturbance rejection, parameter robustness and measurement noise suppression compared with other types of speed controllers. In addition, the proposed digital speed control system in z domain is analyzed in detail. The theoretical effectiveness of the proposed design is verified in a PMSM test rig.